The influence of organizational culture on the performance of STIAMI lecturers through interpersonal communication - Datep Purwa Saputra (Junal Ilmu Manajemen, 2023)
Interpersonal communication is used as a mediator on the indirect influence of organizational culture on the performance of STIAMI Jakarta lecturers. This indirect effect can be determined from the direct influence of organizational culture on the performance of STIAMI Jakarta lecturers, the direct influence of interpersonal communication on the performance of STIAMI Jakarta lecturers and the direct influence of organizational culture on interpersonal communication. This research uses descriptive research method which aims to describe or describe the phenomenon of the influence between the dimensions of organizational culture and interpersonal communication on the performance of STIAMI Jakarta lecturers, either partially or simultaneously. Before determining the regression equation (simple and multiple), the data were tested with validity, reliability, normality, multicollinearity, and heteroscedasticity tests. The significance of the effect of simple partial regression can be determined by using the t-test. By comparing tcount with ttable. If tcount> ttable, it is confirmed that the partial effect is significant and positive. Meanwhile, the simultaneous effect is determined by the F-test. If Fcount>Ftable confirmed multiple regression is significant. The results obtained are all the influences studied, namely, the direct influence of organizational culture on the performance of STIAMI Jakarta lecturers, the direct influence of interpersonal communication on the performance of STIAMI Jakarta lecturers, the direct influence of organizational culture on interpersonal communication. The influence of organizational culture and interpersonal communication together on the performance of STIAMI Jakarta lecturers is positive and significant. The direct influence of organizational culture and interpersonal communication in percent partially on the performance of STIAMI Jakarta lecturers is 47.1% and 15.3%, respectively. The direct influence of organizational culture on work motivation is 9.5%. While the direct influence of organizational culture and interpersonal communication simultaneously is 50.7%.